2020
DOI: 10.14421/csecurity.2020.3.2.2005
|View full text |Cite
|
Sign up to set email alerts
|

MAKING OF DIGITAL FORENSIC READINESS INDEX (DiFRI) MODELS TO MALWARE ATTACKS

Abstract: The increasing number of malware spread in the world today, then there will be more opportunities to commit crime, so readiness is needed for every internet user in dealing with these crimes. The readiness to handle crime is called digital forensic readiness. Therefore, we need a specific digital forensic readiness model to measure the level of readiness of internet users or institutions in achieving malware attacks. This model has the main components used to determine or calculate the level of readiness of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…A digital approach can be used to determine the digital evidence in criminal cases [26] and, in some cases, malware attacks [5], [43]. A recent study reported that digital forensics could be used to prove the case of rife electronic transaction fraud [23].…”
Section: Digital Forensics: Digital Breakthroughs To Uncover the Truthmentioning
confidence: 99%
See 2 more Smart Citations
“…A digital approach can be used to determine the digital evidence in criminal cases [26] and, in some cases, malware attacks [5], [43]. A recent study reported that digital forensics could be used to prove the case of rife electronic transaction fraud [23].…”
Section: Digital Forensics: Digital Breakthroughs To Uncover the Truthmentioning
confidence: 99%
“…In the era of digital, today, anything else needed to prove the evidence in the criminal investigation, including forensic DNA and bioinformatics [4] also cyber or digital forensics [5], because one these digital forensics also can be used for legal evidence-based electronic in criminal justice system [6]. In addition, with bioinformatics, the biological evidence based on DNA analysis can contribute to some biological crimes, such as sexual cases [7], sex identification [8], person or disaster victim identification based on ethnicity [9], [10], determining the quality of DNA by room temperature effect [11], human identification in old skeletal cases [12], child sex trafficking cases [13], ancient DNA analysis [14], a missing person [15], biological relationship reconstruction [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital Forensic Readiness sebagai sebuah komponen dalam keamanan sistem informasi pada suatu organisasi sebagai bentuk keamanan sistem informasi. Model Digital Forensic Readiness Index (DiFRI) untuk mengukur tingkat kesiapan Institusi dalam menanggulangi aktivitas Cyber Crime (Widodo, 2016) dan (Pratama, 2020).…”
Section: Hasil Dan Pembahasanunclassified